2016
DOI: 10.1016/j.mito.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced mitochondrial DNA content on secondary mitochondrial toxicant exposure in Caenorhabditis elegans

Abstract: The mitochondrial genome (mtDNA) is intimately linked to cellular and organismal health, as demonstrated by the fact that mutations in and depletion of mtDNA result in severe mitochondrial disease in humans. However, cells contain hundreds to thousands of copies of mtDNA, which provides genetic redundancy, and creates a threshold effect in which a large percentage of mtDNA must be lost prior to clinical pathogenesis. As certain pharmaceuticals and genetic mutations can result in depletion of mtDNA, and as many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 77 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, they also showed that the effects were NAD + dependent and could be alleviated by pretreatment of the nematodes with exogenous NAD + . In closely related work, Luz and colleagues showed that arsenite caused mitochondrial dysfunction, and that arsenite toxicity was increased in the presence of some, but not all, genetic defects in mitochondrial function (Luz et al 2016a,c;Luz and Meyer 2016). They concluded that the interaction between arsenite toxicity and mitochondrial function was a novel class of interactions first identified in the nematode that needed study in humans.…”
Section: Toxicologymentioning
confidence: 99%
“…Interestingly, they also showed that the effects were NAD + dependent and could be alleviated by pretreatment of the nematodes with exogenous NAD + . In closely related work, Luz and colleagues showed that arsenite caused mitochondrial dysfunction, and that arsenite toxicity was increased in the presence of some, but not all, genetic defects in mitochondrial function (Luz et al 2016a,c;Luz and Meyer 2016). They concluded that the interaction between arsenite toxicity and mitochondrial function was a novel class of interactions first identified in the nematode that needed study in humans.…”
Section: Toxicologymentioning
confidence: 99%
“…However, the degree to which mitochondrial copy number reductions impact cellular health is not well understood, because many cells have high mtDNA redundancy, copy number varies between tissues, and there is a wide range of apparently normal mtDNA copy number in humans (Shokolenko and Alexeyev 2015). We recently found that small decreases in mtDNA copy number have only mild impacts on ATP levels in C. elegans (Luz and Meyer 2016). Nonetheless, mtDNA depletions around 65% can cause disease in humans (Suomalainen and Isohanni 2010), and a certain level of mtDNA is required to pass some developmental milestones in C. elegans (Tsang and Lemire 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This effect, however, is probably small for the other NRTIs as a 55% reduction in mtDNA copy number in C . elegans has recently been shown to have limited influence on life history traits [ 72 ].…”
Section: Discussionmentioning
confidence: 99%